Juridical Analysis of the Sustainability of Marriages Experiencing Prolonged Rifts in the Perspective of Islamic Law and Positive Law in Indonesia - Faricha Uktuvia (Civiliza Publishing, 2026)
Marriage is a social and legal institution that has the purpose of forming a harmonious and sakinah family. But in practice, not all marriages go according to expectations; Many couples face prolonged conflicts that cause serious rifts. These rifts have negative impacts on individuals, children, and the social environment, and raise juridical questions about the feasibility of the continuation of the marriage. This study aims to juridically analyze the continuity of marriages that have experienced prolonged rifts in the perspective of Islamic law and positive law in Indonesia, as well as to compare the principles and mechanisms of conflict resolution in the two legal systems. This study uses normative legal research methods with statute approach, conceptual approach, and case approach. The statute approach is carried out through the study of Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI), while the conceptual approach is used to analyze legal principles such as the purpose of marriage, divorce as the ultimate remedium, and sharia maqashid. The case approach is applied by reviewing religious court decisions related to prolonged domestic conflicts. The data are analyzed qualitatively through descriptive-analytical methods to produce systematic and comprehensive conclusions. The results of the study show that both legal systems, both Islamic law and positive law, emphasize the importance of maintaining the integrity of the household for as long as possible, but still provide room for divorce if the goal of marriage cannot be achieved. Islamic law emphasizes the benefits and prevention of harm through ishlah, tahkim, and divorce as a last resort, while Indonesia's positive law emphasizes formal procedures through the courts with consideration of evidence and legal certainty. Thus, decisions regarding the continuation of marriage must consider the balance between justice, benefit, and protection of individual rights.